Implant loosening following THA with S-ROM prosthesis and subtrochanteric osteotomy: Three case reports - Ma, Yingkai; Ma, Xinnan; Cheng, Shi; Lv, Songcen; Qi, Xin (Frontiers in Surgery, 2023)
Prosthesis loosening after THA is a rather common problem. For DDH patients with CroweIV, the surgical risk and complexity is significant. THA with S-ROM prosthesis combined with subtrochanteric osteotomy is the common treatment. However, In THA, loosening of a modular femoral prosthesis (S-rom) is uncommon and has a very low incidence. With modular prostheses Distal prosthesis looseness are rarely reported. Nonunion osteotomy is a fairly uncommon complication of subtrochanteric osteotomy.  We report three patients with CroweIV DDH who developed loosening of their prosthesis following THA with S-ROM prosthesis and subtrochanteric osteotomy. We address the management of these patients and prosthesis loosening likely underlying causes.